2016
DOI: 10.1139/cjas-2015-0132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alfalfa flavonoids on broiler performance, meat quality, and gene expression

Abstract: Two hundred and forty 1-d-old Arbor Acre female broilers were used to study the effects of alfalfa flavonoids (AF) on broiler performance, meat quality, and gene expression. Chicken were fed with basal diet supplemented with AF at 0, 5, 10, or 15 mg kg −1 diet for a period of 42 d. Growth performance, meat quality, antioxidant effect and lipoprotein lipase (LPL), adipose triglyceride lipase (ATGL), peroxisome proliferator-activated receptor γ (PPARγ), and fatty acid synthase (FAS) gene expressions were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
70
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 38 publications
15
70
1
9
Order By: Relevance
“…In contrast, water holding of chicken meat was improved in a dose‐dependent manner after inclusion of hesperidin (20 mg kg −1 ) in the diet of broilers . Drip loss was also decreased after dietary inclusion (5–15 mg kg −1 ) of alfalfa flavonoids in broiler meat stored for 96 h at 4 °C …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, water holding of chicken meat was improved in a dose‐dependent manner after inclusion of hesperidin (20 mg kg −1 ) in the diet of broilers . Drip loss was also decreased after dietary inclusion (5–15 mg kg −1 ) of alfalfa flavonoids in broiler meat stored for 96 h at 4 °C …”
Section: Discussionmentioning
confidence: 99%
“…19 In contrast, water holding of chicken meat was improved in a dose-dependent manner after inclusion of hesperidin (20 mg kg −1 ) in the diet of broilers. 32 Drip loss was also decreased after dietary inclusion (5-15 mg kg −1 ) of alfalfa flavonoids in broiler meat stored for 96 h at 4 ∘ C. 22 The exact reasons for the discrepancies observed in the literature concerning growth performance parameters and meat quality traits are speculative, but they could be attributable to the different types and levels of flavonoids, periods of supplementation and animal species. Moreover, the variability in the efficacy of flavonoids on growth performance could also be a result, among others, of the basal diet composition, feed intake level, hygienic standards and environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ekstrak daun burahol mengandung senyawa flavonoid meliputi auron, flavanon dan flavanol yang dapat digunakan sebagai antibakteri (Hidayat et al, 2011). Menurut Ouyang et al, (2016) flavonoid dapat meningkatkan ekspresi insulin-like growth factor (IGF1) yang berperan sebagai mediator dalam proliferasi fibroblas dan sintesis kolagen, sehingga memicu pertumbuhan masa otot.…”
Section: Hasil Dan Pembahasanunclassified
“…In vitro tests showed that the flavonoids activated the total and isozymatic activities of SOD, POD, and CAT. Ouyang et al [20] had found that alfalfa flavonoids enhanced the in vivo antioxidant activities (such as SOD, CAT, T-AOC, and GSH-PX) and decreased the level of MDA in serum. In addition, the average daily gain and body weight of the broilers fed with flavonoids were higher than those of broilers fed with basal diet.…”
Section: Introductionmentioning
confidence: 99%